Pengaruh Pakan Fermentasi Terhadap Pertumbuhan Dan Kelangsungan Hidup Ikan Lele (Clarias sp.) - Gea, Rosmawati; Telaumbanua, Dara Dwista; Mendrofa, Osniwati; Gulo, Selvian Suriani; Telaumbanua, Betzy Victor; Dawolo, Januari; Laoli, Destriman; Zebua, Ratna Dewi (Jurnal Perikanan dan Kelautan, 2024)
Feed is an important factor in cultivating catfish (Clarias sp.), which affects the survival and growth of fry. Catfish growth is greatly influenced by feed quality, including nutrition, digestibility and feed utilization. Fermented feed is one of the innovations developed to improve feed quality. Fermented feed has become an attractive alternative to improve feed quality and growth efficiency. This article aims to explore the effect of fermented feed on the survival and growth of catfish fry by reviewing various previous studies. The method used is a literature review by collecting research results from various published scientific articles. The research results show that the use of fermented feed in catfish cultivation can increase growth, digestibility and feed efficiency. Further research is needed to explore optimal dosage and composition.